2000
DOI: 10.4049/jimmunol.165.4.1889
|View full text |Cite
|
Sign up to set email alerts
|

Opening a Window on Thymic Positive Selection: Developmental Changes in the Influence of Cosignaling by Integrins and CD28 on Selection Events Induced by TCR Engagement

Abstract: How TCR and non-TCR signals are integrated by thymocytes to generate a decision to undergo either positive or negative selection remains incompletely understood. Recent evidence suggests that TCR signal transduction changes its quality during thymocyte maturation, but whether the contributions of various cosignaling or costimulatory pathways to thymocyte selection also are modified during development is unclear. Questions also remain about the possible selective roles of specific costimulatory pathways in indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 61 publications
4
28
0
Order By: Relevance
“…To measure the proliferation rate of individual T cell clones, we compared BrdU incorporation by a given TCR Tg clone in different MHC contexts, and by SP thymocytes with different clonotypic Tg TCRs in a given MHC context. Several reports have suggested that the affinity of the AND TCR is higher for I-E k than for I-A b MHC molecules (27)(28)(29). Indeed, this is consistent with the ability of I-E k bound to self peptides to negatively select many Tg thymocytes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…To measure the proliferation rate of individual T cell clones, we compared BrdU incorporation by a given TCR Tg clone in different MHC contexts, and by SP thymocytes with different clonotypic Tg TCRs in a given MHC context. Several reports have suggested that the affinity of the AND TCR is higher for I-E k than for I-A b MHC molecules (27)(28)(29). Indeed, this is consistent with the ability of I-E k bound to self peptides to negatively select many Tg thymocytes.…”
Section: Discussionsupporting
confidence: 75%
“…Although no significant differences in the percentages of CD4SP Tg thymocytes were observed among the three haplotypes, the absolute number of CD4SP thymocytes was 5-fold lower in H-2 k/k mice than in H-2 b/b mice. The small thymus size and the reduction in DP Tg thymocyte numbers observed in the H-2 k/k haplotype are consistent with the induction of a clonal deletion (thymic negative selection) as a result of higher AND TCR affinity for I-E k than for I-A b MHC molecules (27)(28)(29). It has been shown that CD5 surface levels on CD4SP thymocytes from Tg mice increase with TCR affinity for the selecting ligands (30).…”
Section: Proliferation Of Mature Cd4sp Thymocytes Depends On Tcr Affisupporting
confidence: 55%
“…In dispersed cultures of AND TCR transgenic RAG-2 Ϫ/Ϫ thymocytes from mice lacking selecting MHC class II molecule expression (AND DP), CD69 up-regulation can be induced in a cohort of cells without concomitant cell death using transfected ICAM-1 ϩ L cells bearing agonist cytochrome c peptide/I-E k complexes (12,57). These studies did not determine whether these agonist-activated, viable thymocytes are capable of further differentiation and, if so, whether any resulting mature cells would be reactive to the selecting ligand.…”
Section: Cd69 and Bcl-2 Expression Are Up-regulated By Surviving Dp Tmentioning
confidence: 99%
“…Optimal T cell activation requires, in addition, the provision of costimulatory signals imparted by CD4/CD8 coreceptors, CD28 (Lucas & Germain 2000), and cytokine receptors (Curtsinger et al 1999) among others (signal 2), which synergize with primary calcium-dependent TcR-CD3 ligation (signal 1), resulting in induction of the interleukin (IL)-2 autocrine pathway (Germaine 1994), and the temporal expression of cytokine genes and high affinity cytokine receptors (Curtsinger et al 1999, Slifka & Whitton 2000. Signaling through the antigen-specific TcR in conjunction with noncognate costimulatory signals results in the elevation of intracellular calcium and the induction of calmodulin-regulated enzymes, including the serinethreonine phosphatase, calcineurin (Clipstone & Crabtree 1992).…”
Section: An Overview Of Nf-b and Its Role In T Cell Activationmentioning
confidence: 99%